Women’s bodies as dominated territories: Intersectionality and performance in contemporary art from Mexico, Central America and the Hispanic Caribbean - Quiñones-Otal, Emilia (Arte, Individuo y Sociedad, 2019)
Since the 1970s, artists from Central America, Mexico and the Hispanic Caribbean have explored the connection between imperialism and gender violence through innovative artistic proposals. Their research has led them to use the female body as a metaphor for both the invaded geographical territory and the patriarchal incursion into women’s lives. This trend has received little to no attention and it behooves us to understand why it has happened and, more importantly, how the artists are proposing we examine this double violence endured by the women who live or used to live in countries with a colonial present or past. The resulting images are powerful, interesting, and a great contribution to Latin America’s artistic heritage. This study proposes that research yet to be done in other Global areas where colonies has been established, since it is possible that this trend can be understood, not only as an element of the Latin American artistic canon, but also integral to all of non-Western art.